(untitled) (Research, Society and Development, 2022)
Breast cancer is the form that most affects women worldwide, both in developed and developing countries. About 2.3 million new cases were estimated for the year 2020 worldwide, representing approximately 25% of all types of neoplasms diagnosed in women. Incidence rates vary between different regions of the planet, with the highest rates in developed countries. For Brazil, 66,280 new cases of breast cancer were estimated in 2021, with an estimated risk of 61.61 cases per 100,000 women. This study aimed to prepare an updated review of the main methods of treating breast cancer and its consequences on the quality of life of patients. This research is a bibliographic review of the narrative type developed through the search for publications in the databases: Medline, SciELO and Science direct in order to enrich the specialized literature on the importance of dealing with this issue in society. The descriptors were used: breast cancer, treatment, quality of life, chemotherapy, radiotherapy, surgery and immunotherapy. Through the survey carried out in this study, we were able to verify that most treatments are invasive and directly interfere in the socioeconomic aspects and also in the quality of life of the woman. It is concluded that early treatment and reception by the family are of enormous importance for a better quality of life for women during this period, and also the need to carry out further studies on new forms of treatment with less effect on women’s quality of life.